KUANTITAS ANAKAN KULTUR SEMUT RANGRANG, Oecophylla smaragdina, SECARA ARTIFISIAL DENGAN MENGGUNAKAN BEBERAPA JENIS PAKAN BERBEDA - Lintang Dianing Ratri; Edi Basuki; Darsono Darsono (Scripta Biologica, 2017)
Oecophylla smaragdina or weaver ants is social insect that has an important role in the ecosystem. One of its main function is as a biological control agent in agriculture. The use of weaver ants in an effort to develop a biocontrol continues and increases, this has caused the significant decrease of the natural population of O. smaragdina. Therefore, the weaver ants rearing is needed to maintain its existence in natural habitat without excessive exploitation. The purpose of this study were to determine the effect of different types of feed i.e. snails, earthworms, and okara (tofu by-product) in the production of weaver ants kroto; and to determine the different of treatments of feeds provided to the production quantity of weaver ants kroto. The experimental method used in this study with a completely randomized design. Treatment was given by different protein sources feeding i.e. snails (Pomacea canaliculata), earthworm (Lumbricus rubellus), and okara. Five replicates were appliead for each treatment. Earthworms fed ants produced highest number of kroto with total of 1,030 individuals and weight 87.4 gram in total. Snails fed ants produced 866 individuals and weight 73.1 gram. Okara fed ants produced 543 individuals and weight 45.9 gram.